2022
DOI: 10.1002/psp4.12764
|View full text |Cite
|
Sign up to set email alerts
|

Increasing application of pediatric physiologically based pharmacokinetic models across academic and industry organizations

Abstract: There has been a significant increase in the use of physiologically based pharmacokinetic (PBPK) models during the past 20 years, especially for pediatrics.The aim of this study was to give a detailed overview of the growth and areas of application of pediatric PBPK (P-PBPK) models. A total of 181 publications and publicly available regulatory reviews were identified and categorized according to year, author affiliation, platform, and primary application of the P-PBPK model (in clinical settings, drug developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…Pediatric PBPK modeling matures rapidly. In 2020, the number of scientific publications on pediatric PBPK modeling was 34 compared to one publication in 2005 [ 28 ]. Yet, many more physiology and compound models are available in repositories.…”
Section: A Pragmatic Pbpk Modeling Approachmentioning
confidence: 99%
“…Pediatric PBPK modeling matures rapidly. In 2020, the number of scientific publications on pediatric PBPK modeling was 34 compared to one publication in 2005 [ 28 ]. Yet, many more physiology and compound models are available in repositories.…”
Section: A Pragmatic Pbpk Modeling Approachmentioning
confidence: 99%
“…When clinical lactation data are available, some of the uncertainty associated with extrapolation of the infant daily dose is removed. Here, we present two case studies where observed milk concentrations were available and the extrapolated infant daily dose was used to simulate plasma concentration time profiles in infants using a pediatric PBPK model (Johnson et al 2 ); one involves a drug–drug interaction for a combination therapy, and the other, the complex interplay between mother/infant and the impact of their respective CYP2B6 genotypes.…”
Section: Predicting Drug Concentrations In Infants During Breastfeedingmentioning
confidence: 99%
“…Although knowledge gaps remain, ongoing research relating to these processes in children, has allowed refinement of relevant physiological parameters and integration of more complex models. Thus, PBPK models which are increasingly used in pediatric clinical pharmacology, including drug development, are reaching maturation for applications with high regulatory impact 2 . In this paper, we discuss how “off the shelf” PBPK models for commonly used drugs, already robustly verified in terms of their disposition, can be used to assess safety concerns in breastfeeding infants as a consequence of the nursing mothers taking medication(s).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations